Agents of (un)sustainability: democratising universities for the planetary crisis - McGeown, Calum; Barry, John (Frontiers in Sustainability, 2023)
As producers and gatekeepers of knowledge, and as providers of education and training, our universities play a key role in the reproduction of unsustainability. This article finds that they are, as currently organised, therefore complicit in frustrating and delaying action to address the planetary crisis. However, as highly resourced and influential institutions, they have an inherently transformative potential, should their resources and activities be redirected towards progressive social and ecological ends, which challenge rather than support the unsustainable status quo. This means that, as workers within these institutions, academics and researchers are faced with a choice: to be agents of this reproduction or to be advocates and activists for change. We argue for the latter. In doing so, we seek to build on the analysis and demands of emergent movements such as Fossil Free Research, Faculty for a Future and Scientist Rebellion in making the case for universities to show leadership on listening to the very science they produce on the planetary emergency, and act accordingly. Employing a green political economy critical analysis, the article suggests that, if they are to contribute to societal transformation, universities themselves must undergo transformations that explicitly and systematically reorient academic practices around social and ecological protection and priorities. Building on these findings, it lays out a series of normative and practical arguments for a broad programme of democratisation around three pillars of academic practise: (1) Research, (2) Education and (3) Outreach and engagement. However, any such processes will of course be difficult, especially given the wider neoliberal political and political economy context within which universities operate, as well as a conservative institutional culture which disincentivises dissent from “business as usual”. In the discussion that follows, we therefore anticipate and argue that advancing such transformative and innovative changes will initially involve individuals or small groups of academics willing to go beyond “academia as usual”.